Prevalence, pattern and distribution of non-syndromic tooth agenesis in permanent dentition among Malaysian population - Fauzi, Nurul Hasyiqin; Lestari, Widya; Kharuddin, Azrul Fazwan; Ardini, Yunita Dewi (Elsevier, 2019)
Tooth agenenesis is reduction of tooth number caused by congenitally failure of tooth development causing hypodontia and oligodontia. The prevalence, pattern and distribution are varies by populations. The aim of this study was to identify the pattern and distribution of tooth agenesis in permanent dentition among Malaysian population. Patients were in the range of 12 until 60 years old has missing average of 2 teeth missing. Excluding third molar, the prevalence of population under study was 1.005%. Mandibular and/or lateral incisors (28%) were identified as the most common missing tooth. There were no significant difference between missing tooth between male and female (p=0.265). More missing teeth were observed at maxilla jaw (54.67%), right side (54.67%), posterior region (53.33%) and missing unilaterally (71.42%). Some tooth anomalies such as peg shaped tooth (8.57%) and microdontia (5.71%) also presented. In conclusion, the prevalence studied population was lower than normal range and previous studies conducted in Malaysian but still may presumably represent group of population under study, while mild hypodontia is considered as the most common type of tooth agenesis. The most common missing tooth is lateral incisors whereas mild hypondontia is identified the most common tooth agenesis.